2014
DOI: 10.1007/s12550-014-0189-z
|View full text |Cite
|
Sign up to set email alerts
|

The major volatile compound 2-phenylethanol from the biocontrol yeast, Pichia anomala, inhibits growth and expression of aflatoxin biosynthetic genes of Aspergillus flavus

Abstract: Aspergillus flavus is a ubiquitous saprophyte that is able to produce the most potent natural carcinogenic compound known as aflatoxin B1 (AFB1). This toxin frequently contaminates crops including corn, cotton, peanuts, and tree nuts causing substantial economic loss worldwide. Consequently, more than 100 countries have strict regulations limiting AFB1 in foodstuffs and feedstuffs. Plants and microbes are able to produce volatile compounds that act as a defense mechanism against other organisms. Pichia anomala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(107 citation statements)
references
References 20 publications
5
101
0
1
Order By: Relevance
“…As a control, no PI staining in the nucleus was detected in the strain with or without PEA treatment (Figure 8A), consistent with results on conductivity, suggesting that the hyphae were intact (Figure 8B). Similar result was found in hyphae of Aspergillus flavus in the presence of PEA [32].
Figure 8 Effect of PEA on hyphal cytomembranes.
…”
Section: Resultssupporting
confidence: 81%
“…As a control, no PI staining in the nucleus was detected in the strain with or without PEA treatment (Figure 8A), consistent with results on conductivity, suggesting that the hyphae were intact (Figure 8B). Similar result was found in hyphae of Aspergillus flavus in the presence of PEA [32].
Figure 8 Effect of PEA on hyphal cytomembranes.
…”
Section: Resultssupporting
confidence: 81%
“…In recent years, many plant‐based natural products which are safer than synthetic products are considered as an alternative to these chemical fungicides and preservatives. Many researchers have reported the inhibitory role of cinnamon, citral, litsea, ginger, clove, eucalyptus, anise, spearmint, and camphor oils against different microbial species (Chao and others ; Velluti and others ; Patil and others ; Yamamoto‐Ribeiro and others ; Hua and others ). Among the plant‐based natural compounds, cinnamaldehyde is highly effective in inhibiting A. flavus growth and aflatoxin production, followed by eugenol and citral in our earlier study (Yuan and others ).…”
Section: Discussionmentioning
confidence: 99%
“…Certain natural compounds can inhibit aflatoxins production by reducing the expression of the aflatoxin gene pathway. For example, curcumin inhibits AFB 1 production in A. parasiticus by down regulating the expression of aflM ( ver‐1 ), aflD ( nor‐1 ), aflC ( pksA) , aflP ( omtA ), and aflR (Jahanshiri and others ); Zataria multiflora Boiss (which is known as Avishan Shirazi, a valuable Iranian medicinal plant) essential oil down regulates the gene expression of aflD , aflM , and aflP in A. parasiticus (Yahyaraeyat and others ); 2‐phenylethanol down regulates the structural genes ( aflC , aflD , aflO ( omtB ), and aflM ) involved in aflatoxin biosynthesis (Hua and others ); and cocultivation of A. flavus with Bacillus megaterium down regulates the aflatoxin pathway genes ( aflF , aflT , AflJ , aflL , and aflX ) (Kong and others ).…”
Section: Introductionmentioning
confidence: 99%
“…A biocontrol yeast, Pichia anomala strain WRL-076, inhibited A . flavus spore germination and aflatoxin production [27]. Sangmanee and Hongpattarakere [28] reported that Lactobacillus plantarum K35 isolated from traditional Thai fermented rice noodles could effectively inhibit the growth and aflatoxin production of A .…”
Section: Introductionmentioning
confidence: 99%